Skin appendageal immune reactivity in a case of cutaneous lupus - Ana Maria Abreu Velez; A. Deo Klein; Michael S. Howard (Our Dermatology Online, 2011)
Background: Discoid lupus erythematosus is a cutaneous disease with a worldwide distribution, and its pathogenesis remains unclear. Case Report: A 41 year old male was evaluated for hair loss, in patches on the scalp. We studied selected adaptor proteins expressed in T, natural killer, neutrophil and mast cells; these proteins are important mediators for antigen receptor signaling in situ. Methods: Skin biopsies for hematoxylin and eosin examination, as well as for direct immunofluorescence and immunohistochemistry analysis were performed. Results: Hematoxylin and eosin staining demonstrated classic features of lupus with focal dermal scarring; epidermal atrophy was noted, with lymphohistiocytic infiltrates around the skin appendages. Direct immunofluoresence revealed classic, lupus band positive staining along the dermal/epidermal junction. In addition, immune reactants were identified in neurovascular areas, and around pilosebaceous units. Immunohistochemistry staining showed positive staining for the T-cell antigen receptor zeta chain, the linker for activation of T cells, myeloperoxidase, cyclo-oxygenase 2, melanoma-associated antigen 1, B cell leukemia/lymphoma-2 associated X protein, and BCL-2 markers. The positive staining was observed within the dermal inflammatory infiltrate, around pilosebaceous units, upper dermal blood vessels, and focally within eccrine sweat glands. Conclusions: The pathobiology of cutaneous lupus involves not only the epidermis, but also dermal pilosebaceous units, eccrine sweat glands and blood vessels. Further studies are recommended, especially in the light of presented data regarding T cell activation and proapototic molecules.